Global perspectives on disability activism and advocacy our way - Soldatic, Karen; Johnson, Kelley, 1947- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
This book explores the diverse ways in which disability activism and advocacy are experienced and practised by people with disabilities and their allies. Contributors to the book explore the very different strategies and campaigns they have used to have their demands for respect, dignity and rights heard and acted upon by their communities, by national governments and the international community. The book, with its contemporary global focus, makes a significant contribution to the field of disability and social justice studies, particularly at a time of major social, political and cultural upheaval. Global Perspectives on Disability Activism and Advocacy offers a significant intervention within the field of disability at a time of major social upheaval where actors, advocates and activists are seeking to hold onto existing claims for rights, equality and disability justice.
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- Political activity; People with disabilities -- Government policy; SOCIAL SCIENCE / Handicapped; POLITICAL SCIENCE / Political Process / Political Advocacy